2011
DOI: 10.1002/jcp.22743
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow and peripheral white blood cells number is affected by sleep deprivation in a murine experimental model

Abstract: Sleep deficit and related disorders are becoming increasingly prevalent in modern life and an extensive literature has documented that acute or chronic sleep deprivation can lead to several physiological consequences. Here, we evaluated the effects of sleep deprivation on hematopoietic composition of either bone marrow or peripheral blood. Mice were subjected to paradoxical sleep deprivation (PSD) for 72 h by modified multiple platform method, with or without an additional sleep recovery (SR) period of 10 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…F) confirms the SD‐induced alterations in medullary B lymphopoiesis verified by flow cytometry analysis, based on the diminishing percentage of both lymphoid progenitors and mature B lymphocytes. This finding is in line to the observed effect of SD on lymphocyte clonogenicity (Guariniello et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…F) confirms the SD‐induced alterations in medullary B lymphopoiesis verified by flow cytometry analysis, based on the diminishing percentage of both lymphoid progenitors and mature B lymphocytes. This finding is in line to the observed effect of SD on lymphocyte clonogenicity (Guariniello et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies in the field of sleep have shown the importance of this behavioral state for the homeostasis of the immune system. SD can result in many losses concerning the bidirectional communication of the immune system with the nervous and endocrine systems (Lange et al, , ; Motivala, ; Reis et al, ), reduction in the weight of the lymphoid organs (Zager et al, ) and disruption of the homeostasis of immune cells (Zager et al, ; Guariniello et al, ; Lungato et al, ; Maragno‐Correa et al, ). In this study, it was found that the total populations of B lymphocytes in the spleen tissue were reduced after 72 h of SD (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous research in patients undergoing standard-dose chemotherapy suggests that sleep disruption occurs first in a cascade of symptoms, contributing to increases in fatigue and in turn, depression (71). In addition, preliminary research suggests that sleep disruption may negatively impact immune response and reconstitution (72), although this has not been demonstrated in the context of HCT. Taken together, these studies argue for early intervention to manage sleep disruption and disorders in HCT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…For PSD experiments, the animals were randomly assigned into three groups: the control group, the PSD group and the PSR group. PSD animals were sleep deprived for 72 consecutive hours, using the multiple platform method as previously described [3,13,14,15]. The PSR mice were sleep deprived for 72 consecutive hours followed by 24 h in sleep rebound period.…”
Section: Methodsmentioning
confidence: 99%